Quality of life outcomes in cryoablation of atrial fibrillation–A literature review. Issue 10 (25th August 2021) - Vandenberk, Bert; Lauwers, Laurens; Robyns, Tomas; Garweg, Christophe; Willems, Rik; Ector, Joris; Haemers, Peter
Abstract: Background: Cryoballoon ablation (CRYO) for pulmonary vein isolation (PVI) in atrial fibrillation (AF) has become an established treatment option as alternative for radiofrequency catheter ablation (RFCA). As symptom relief is still the main indication for PVI, quality of life (QoL) is a key outcome parameter. This review summarizes the evidence about the evolution of QoL after CRYO. Methods: A search for clinical studies reporting QoL outcomes after CRYO was performed on PUBMED and COCHRANE . A total of 506 publications were screened and 10 studies met the in‐ and exclusion criteria. Results: All studies considered QoL as a secondary endpoint and reported significant improvement in QoL between baseline and 12 months follow‐up, independent of the QoL instruments used. The effect size of CRYO on QoL was comparable between studies and present in both paroxysmal and persistent AF. Direct comparison between CRYO and RFCA was limited to two studies, there was no difference between ablation modalities after 12 months FU. Two studies in paroxysmal AF reported outcome beyond 12 months follow‐up and QoL improvement was maintained up to 36 months after ablation. There were no long‐term data available for persistent AF. Conclusion: CRYO of AF significantly improves QoL. The scarce amount of data with direct comparison between subgroups limits further exploration. Assessment of QoL should be considered a primary outcome parameter in future trials with long‐term follow‐up.